Influence of iodine impurity on photochemical and emission processes in CdBr₂:Cu crystals - Novosad, S.S.; Novosad, I.S. (Functional Materials, 2004)
Influence of iodine impurity on photochemical and emission processes in CdBi^Cu crystals have been studied under N₂ laser and X-ray excitation. After the materials irradiation by the integral emission of a deuterium lamp at 295 K, additional bands peaked near 395 and 625 nm were revealed that are due to Cu²⁺ and nCu⁰ centers, respectively. The photochemical transformations in those systems have been shown to be related mainly to changes in the charge state of copper centers. UV irradiation of CdBr₂:Cu,l results in decreased X-ray luminescence intensity in the non-elementary 510 nm band, weakened 620 nm band and increased intensity of the photoluminescence band peaked at 490-500 nm at 85 K. After the colored samples were heated to about 300 °C, no features due to the photochemical transformations have been observed in the spectral characteristics. The emission band peaked at 490 to 500 nm is related to the emissive annihilation of excitons localized at l_ ions. The photoluminescence in the 620 nm band is supposed to be due to complex centers containing anion vacancies and iodine ions. Исследовано влияние примеси иода на фотохимические и излучательные процессы в кристаллах CdBr^Cu при возбуждении ^-лазером и рентгеновским излучением. После облучения материалов при 295 К интегральным светом дейтериевой лампы в спектрах поглощения выявлены дополнительные полосы с максимумами около 395 и 625 нм, которые обусловлены Cu²⁺ и nCu⁰ -центрами, соответственно. Показано, что фотохимические преобразования в этих системах, в основном, связаны с изменением зарядового состояния медных центров. Действие УФ-света на CdBr₂:Cu приводит к уменьшению интенсивности рентгенолюминесценции в неэлементарной полосе 510 нм, ослаблению полосы 620 нм и увеличению интенсивности полосы с максимумом в области 490500 нм фотолюминесценции при 85 К. После прогрева окрашенных образцов до температуры ~300°С особенности, вызванные фотохимическими преобразованиями, в спектральных характеристиках не проявляются. Полоса излучения с максимумом в области 490-500 нм связана с излучательной аннигиляцией экситонов, локализированных на ионах l_. Фотолюминесценция в полосе 620 нм приписывается сложным центрам, в состав которых входят анионные вакансии и ионы иода. Вивчено вплив домішки йоду на Фотохімічні та випромінювальні процеси в кристалах CdBi^Cu при збудженні І^-лазером та рентгенівським випромінюванням. Після опромінення матеріалів при 295 К інтегральним світлом дейтерієвої лампи у спектрах поглинання виявлено додаткові смуги з максимумами близько 395 і 625 нм, які зумовлені Cu²⁺ і nCu⁰ - центрами, відповідно. Показано, що фотохімічні перетворення у цих системах, в основному, пов’язані зі зміною зарядового стану мідних центрів. Дія УФ-світла на CdBi^CuJ приводить до зменшення інтенсивності рентгенолюмінесценції у неелементарній смузі 510 нм, послаблення смуги фотолюмінесценції 620 нм та підсилення інтенсивності смуги фотолюмінесценції з максимумом в області 490-500 нм при 85 К. Після прогріву забарвлених зразків до температури ~300°С особливості, викликані фотохімічними перетвореннями, в спектральних характеристиках не проявляються. Смуга випромінювання з максимумом в області 490-500 нм пов’язується з випромінювальною анігіляцією екситонів, локалізованих на іонах І_. Фотолюмінесценція в смузі 620 нм приписується складним центрам, в склад яких входять аніонні вакансії та іони йоду.